"The Industrious Exiles of Erin": Irish Immigrants in Mid-Nineteenth Century St. Stephen, New Brunswick, and Calais and Baring, Maine. Issue 2 (3rd April 2018) - Lane, Hannah M.
ABSTRACT: In the mid-nineteenth century, St. Stephen, New Brunswick, and Calais, Maine, Irish cultural institutions developed earlier on the New Brunswick side of the border, but until the late 1860s, nativism was more public and organized in Maine. Census returns linked to parish assessments show that although Irish immigrant men were poorer than men born in Maine or New Brunswick, differences between Irish Catholics and Irish Protestants within the youngest and oldest age groups were much narrower than has sometimes been assumed in popular cultural memory.